Peran Kepercayaan Konsumen dalam Memediasi Pengaruh Harga dan Tingkat Penilaian Konsumen terhadap Minat Beli Busana Adat Bali - Ni Kadek Raytha Susan Julianti; Putu Dyah Permatha Korry (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
This study aims to analyze the role of consumer trust in mediating the influence of price and consumer ratings on online purchase intention of Balinese traditional clothing. Using an explanatory quantitative approach, the research was conducted in Badung Regency involving 160 respondents who have purchased Balinese traditional clothing online. Data were collected through questionnaires and analyzed using PLS-SEM. The results show that: (1) price has no significant direct effect on purchase intention; (2) consumer rating has a positive and significant effect on purchase intention; (3) both price and rating have a positive significant effect on consumer trust; and (4) consumer trust has a positive significant effect on purchase intention. Furthermore, consumer trust acts as a full mediator between price and purchase intention, and as a partial mediator between rating and purchase intention. These findings indicate that in the context of digitally marketed cultural products, consumer trust is a key factor more critical than direct price considerations. This study provides a theoretical contribution to digital consumer behavior literature for traditional products and practical implications for MSMEs to build trust through price transparency, improved product quality, and management of positive reviews to enhance purchase intention.